Vortex Streets on a Sphere - Alobaidi, Ghada; Mallier, Roland (Journal of Applied Mathematics, 2011)
We consider flows on a spherical surface and use a transformation to transport some well-known periodic two-dimensional vortex streets to that spherical surface to arrive at some new expressions for vortex streets on a sphere.